Camisea gas savings by use of a combined cycle gas power and steam power generation - Salas Colotta, Gilberto (2010)
A combined cycle is characteristic of a power producing engine or plant that employs more than one thermodynamic cycle. Heat engines are only able to use a portion of the energy their fuel generates (usually less than 30%). The remaining heat from combustion is generally wasted. Combining two or more “cycles” such as the Brayton cycle and Rankine cycle results in improved overall effi ciency. In a combined cycle power plant (CCPP), or combined cycle gas turbine (CCGT) plant, a gas turbine generator generates electricity and the waste heat is used to make steam to generate additional electricity via a steam turbine; this last step enhances the effi ciency of electricity generation.